Analysis of Student Learning Style Tendencies Reviewed from Learning Independence in Physics Learning - Rosdianto, Haris; Wijaya, Andika Kusuma; Haidir, Risa (STKIP Singkawang, 2025)
The research aims to 1) describe student learning style profiles; 2) describe the profile of student learning independence in physics learning; 3) describe the tendencies of learning styles of SMPN student in Singkawang City in terms of learning independence in physics learning. This type of research is survey research using descriptive data analysis techniques where research data will be displayed using pie charts and tables. Respondents in this study were taken using a cluster sampling technique from the entire population, which is all syate junior high school students in Singkawang City. The data collection technique used in this research uses a questionnaire, namely a questionnaire on student learning style tendencies and a questionnaire on learning independence in physics learning. The research results show that the combination of multimodal learning style (65%) dominates unimodal learning style (35%). Based on the type learning style, it shows that 1 in 3 respondents have the VARK learning style, which makes it the most dominant type. The distribution of learning independence data forms a bell curve indicating that the data distribution tends to be normal. Analysis of learning style data in terms of the learning independence category shows that there is tendency for the VARK learning style type to be dominant in each category.